ISLAMIC VALUES IN R.J PALACIO’S “WONDER” - Ariyanti Safina Panjaitan; Diana Sopha; Vera Kristiana (PHILOLOGY Journal of English Language and Literature, 2021)
The main problems of this research are to find the islamic values found in R.J Palacio’s “wonder”. The study used the descriptive qualitative research method. The subject of this research was R.J Palacio’s “Wonder”. The primary data of this research were experssions in words, sentences, qoutation and paragraph related to Islamic Values of manners and islamic Values of behaviour in the novel. The supporting data were obtained from some sources, such as book, article, journal and film related to manners and behaviour. In collecting data, read-write technique was used. The data analysis was conducted using islamic values approach. The result of this research show two important points. First, there are 4 types islamic values of manners that found in the novel reflected by Augie (protagonist). The second there are 4 types islamic values of behaviour in novel reflected by Augie (protagonist) namely: his behaviour towards friends explained about fairing to his friend, Augie’sbehaviour towards others explained about thangking to those who helped him and helping friend when it’s hard or happy. Augie’sbehaviour towards the elder and young people explained about how Augie’s talk to talk with older people more than him, Augie’sbehaviour toward his parents explained about his obidient and always make his parents happy.